Distribution of benthos in the Nila River, Kerala, India - Sushama, S; Tresa, Radhakrishnan (Indian Journal of Fisheries, 2016)
The Nila River, which is the second longest river in Kerala was surveyed from April 1998 to March 1999 for benthic fauna. Dipteran larvae and oligochaetes were the dominant groups throughout the freshwater stretches of the river. In the estuarine zone, polychaetes were dominant. Benthic fauna was poor in the Nila River possibly because of the homogenous nature of the substratum, fast flowing nature of the river and constant disturbance caused by sand mining activities.